A conservação preventiva de acervos têxteis: uma “checklist” aplicada ao Museu Municipal Parque da Baronesa (MMPB) – Pelotas/RS - Martins, Larissa Tavares (2015)
This research is the result of a study conducted at the Museu Municipal Parque da Baronesa (MMPB) - Pelotas / RS, which aims to analyze the preventive conservation actions developed in the textile collection of the museum institution. It has as its central theme the conservation of MMPB pieces trying to identify the practices carried out in relation to the handling, packaging and storage of textile collections. The main objective of this study is to propose a data collection instrument in the form of a checklist, seeking to verify the actions in relation to textiles. Through this research we aim to highlight the importance of preventive maintenance on one of the elements that makes up part of history, representing an entire path taken by Pelotas society both on a local, regional and even national. As the final product a Preventive Conservation of Collections Manual Textiles will be made, where the objective is that this is a practical guide containing the optimal ways to handle, pack and store the pieces of fabric. It is concluded that the practices exercised by MMPB are considered satisfactory, but a series of adjustments and interventions have yet to be developed. It is intended however; to contribute to the debate about the importance of preventive conservation of historical collections in institutions, encouraging the safeguard of the existing textile heritage in museums.